Mapping evidence of free maternal healthcare financing and quality of care in sub-Saharan Africa: a systematic scoping review protocol - Ansu-Mensah, Monica (Health Res Policy Syst, 2019)
BACKGROUND: Identifying and addressing research gaps on the implementation of free maternal healthcare financing policies and the quality of service delivery in sub-Saharan Africa (SSA) is essential in ensuring continuous patronage of the services by clients and sustainability of the policies to meet the intended goals. The proposed scoping review is aimed at mapping evidence on free maternal healthcare financing and quality of care in SSA. METHODS: Arksey and O’Malley’s framework, Levac and colleagues’ recommendations, and the Joanna Briggs Institute guidelines will be used to guide the proposed study. A complete keyword search for relevant studies presenting evidence on free maternal healthcare financing and perceived quality of care among women in SSA will be performed in EBSCOhost, PubMed, Web of Science, Google Scholar and SCOPUS. Relevant grey literature from university repositories and international organisations such as WHO and government websites, and the reference lists of included studies will be additionally searched. The Preferred Reporting Items for Systematic Reviews and Meta-analysis: Extension for Scoping Review (PRISMA-ScR) will be used to present the results of the proposed scoping review. NVivo version 11 software package will be employed to extract the relevant outcomes from the included studies using content thematic analysis. Quality appraisal of the included studies for this proposed study will be performed utilising the latest mixed methods appraisal tool. DISCUSSION: It is anticipated that the results of the proposed study will inform future research and reveal evidence-based information to address potential quality of care issues that may arise because of free maternal healthcare policy implementation in some SSA countries. The proposed study will also be useful to other SSA countries planning to implement free maternal health policy, as they will be able to draw useful lessons to guide them through the process.